2020
DOI: 10.1101/2020.01.31.929786
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metagenomic Insights into Microbial Metabolisms of a Sulfur-Influenced Glacial Ecosystem

Abstract: 25Biological sulfur cycling in polar, low-temperature ecosystems is an understudied 26 phenomenon in part due to difficulty of access and the ephemeral nature of such environments. 27 One such environment where sulfur cycling plays an important role in microbial metabolisms is 28 located at Borup Fiord Pass (BFP) in the Canadian High Arctic. Here, transient springs emerge 29 from the toe of a glacier creating a large proglacial aufeis (spring-derived ices) that are often 30 covered in bright yellow/white su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 87 publications
(128 reference statements)
0
1
0
Order By: Relevance
“…Full-length sequences permitted a more precise taxonomic assignment of the most abundant community members as well as 14 minor taxa with relative abundance ranging from 0.05 to 1%. Many of these taxa are closely related to psychrotolerant strains, including a member of Brevundimonas, a taxon detected in the Arctic (Trivedi et al, 2018) and Antarctic (González-Toril et al, 2009) and which is known to be resistant to cold temperatures (Dartnell et al, 2010) and the genus Pedobacter, also found in Arctic environments (Zhou et al, 2012;Peter and Sommaruga, 2016;Trivedi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Full-length sequences permitted a more precise taxonomic assignment of the most abundant community members as well as 14 minor taxa with relative abundance ranging from 0.05 to 1%. Many of these taxa are closely related to psychrotolerant strains, including a member of Brevundimonas, a taxon detected in the Arctic (Trivedi et al, 2018) and Antarctic (González-Toril et al, 2009) and which is known to be resistant to cold temperatures (Dartnell et al, 2010) and the genus Pedobacter, also found in Arctic environments (Zhou et al, 2012;Peter and Sommaruga, 2016;Trivedi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%